Effect of bioglass addition on the properties of HA/BG composite films fabricated by pulsed laser deposition. Issue 12 (15th August 2018) - Wang, D.G.; Chen, C.Z.; Yang, X.X.; Ming, X.C.; Zhang, W.L.
Abstract: In order to improve the osteoconduction of metallic implants, bioactive films are often coated on the implant surfaces. In this paper, hydroxyapatite (HA) and bioglass (BG) composite films on Ti alloy were fabricated by pulsed laser deposition, and the effect of bioglass addition on the film properties was analyzed. Results show that the composite films are composed of crystalline HA, β-TCP and amorphous bioglass. The addition of bioglass decreases the crystallinity of the whole film and increases the Ca/P and Si/Na atomic ratio change rate. However an appropriate addition of bioglass can increase the adhesion strength to substrate and induce the c-axis orientation growth of HA. The composite film with 20 wt% bioglass exhibits excellent osteoconduction and can be considered as a prospective competitor for bone implantology applications.